Public awareness of and action towards heart attack symptoms: an exploratory study in Kuantan, Pahang - Al-Shami, Abdulkareem Mohammed; Ahmed, Abdullah Abdulmajid Abdo; Jamshed, Shazia Qasim; Fata Nahas, Abdul Rahman (Wolters Kluwer - Medknow, 2020)
Background: Awareness of symptoms and action towards heart attack (HA) are very important to reduce the deaths and disability. The current research aimed to assess the awareness of symptoms and action towards heart attack among the general public. Methods: A cross-sectional study was designed, and a convenience sample method was used to select respondents in Kuantan from May to July 2018. Results: A total of 393 respondents were recruited. The actual proportions associated with respondents who have been aware of heart attack symptoms ranged through 26.35% (pain or discomfort in the jaw, neck or back) to 71.65 % (chest pain or discomfort). From the respondents, 35.6% would call ambulance if they see someone suffering from heart attack symptoms, 82% realized ≥ 1 symptom, 11.5% recognized all five HA symptoms and 1.3% had excellent awareness (correct recognition of all five HA symptoms, without response “Yes” to decoy question as well as correctly determining call ambulance if someone showed symptoms of HA). Participants who have diabetes and hypercholesteremia were more likely to recognize all five-heart attack symptoms than others without. The odds ratio (OR) for those who have an excellent awareness of all five HA was significantly higher with those who single (OR 0.023; 95% Cl 0.001-0.594) than others who widowed, married and divorce, as well as for participants who were Malay (OR 0.376; 95% Cl, 0.193-0.733). Furthermore, OR for participants who have a history of HA among relatives included neighbors (OR 2.206; 95% CI, 0.983-4.949), those received information associated with HA (OR 7.540; 95% CI, 2.037-27.914) and being aware HA requires quick treatment (OR 0.176; 95% CI 0.044-0.710). Conclusion: Awareness of heart attack symptoms and proper action seem to be poor in Malaysia. Educational interventions to increase general awareness among the lay public, specifically in the elderly and who are at high risk for cardiovascular diseases are recommended.